Prevalence and Susceptibility Pattern of Bacterial Uropathogens among Patients with Urinary Tract Infection at Birat Medical College Teaching Hospital of Eastern Nepal - Dewasy, Bijoylakshmi; Singh, Randhir Kumar; Parajuli, Surya Bahadur; Kafle, Tara; Mishra, Anjali (Birat Journal of Health Sciences, 2020)
Introduction Urinary tract infection (UTI) is a frequent condition encountered in clinical settings. Empirical treatment is common. The treatment without urine culture and sensitivity leads to antimicrobial resistance. This is a major global concern.Objective The objective of this study was to find the prevalence and susceptibility pattern of Bacterial Uropathogens among patients with Urinary Tract Infection at Birat Medical College and Teaching Hospital of eastern Nepal.Methodology A cross-sectional study was conducted among patients with UTI attending Birat Medical College and Teaching Hospital from August 2018 to December 2018. The sample size of the study was 530. Ethical clearance was taken from the Institutional Review Committee of Birat Medical College and Teaching Hospital (Ref: IRC-PA-009/2075-76). Data were entered into Microsoft Excel and analyzed by using SPSS.Results The prevalence of bacterial uropathogens among urine culture was 66.04%. The common uropathogens isolated were E.coli (66.9%) and Klebsiella spp (15.1%). E.coli was highly susceptible to Chloramphenicol (100%) followed by Ceftrixone (82.4%), Cefpodoxime (77.8%) and Amikacin (77.9%); while Klebsiella spp were susceptible to nalidixic acid (40%) followed by co-trimoxazole (17.9%).Conclusion Almost 2 out of 3 samples had bacterial uropathogens isolated. E. coli and Klebsiella spp were common. Chloramphenicol and Nalidixic acid were highly susceptible to E.coli and Klebsiella spp respectively.